NUMB maintains bone mass by promoting degradation of PTEN and GLI1 via ubiquitination in osteoblasts. (December 2018) - Ye, Ling; Lou, Feng; Yu, Fanyuan; Zhang, Demao; Wang, Chenglin; Wu, Fanzi; Li, Xin; Ping, Yilin; Yang, Xiao; Yang, Jing; Chen, Dian; Gao, Bo; et al.
Abstract The adaptor protein NUMB is involved in asymmetric division and cell fate determination and recognized as an antagonist of Notch. Previous studies have proved that Notch activation in osteoblasts contributes to a high bone mass. In this study,   however,  an osteopenic phenotype was found in 9-week-old mice using osteoblastic specific Col1a1–2.3-Cre to ablate bothNumb and its homologueNumbl . The trabecular bone mass decreased dramatically while the cortical bone mass was unaffected. Here, the Notch signal was not activated, while the tensin homologue deleted on human chromosome 10 (PTEN), which dephosphorylates phosphatidylinositide 3-kinases, was elevated, attenuating protein kinase B (Akt). The ubiquitination assay revealed that NUMB may physiologically promote PTEN ubiquitination in the presence of neural precursor cell-expressed developmentally downregulated protein 4–1. In addition, the deficiency ofNumb /Numbl also activated the Hedgehog pathway through GLI1. This process was found to improve the ratio of the receptor activator of nuclear factor-kB ligand to osteoprotegerin, which enhanced the differentiation of osteoclasts and bone resorption . In conclusion, this study provides an insight into  new functons of   NUMB and NUMBL on bone homeostasis. Homeostasis: Protein regulators of bone mass The related proteins NUMB and NUMBL maintain the survival of bone-generating osteoblast cells. NUMB was previously recognized to antagonize Notch signaling pathway ; In this study, it observes  that genetically altered mice, unable to express the two proteins, suffered from degraded bone quality. This suggests that the two proteins play a more complex, nuanced role in the process of bone mass maintenance. The team's studies showed that NUMB and NUMBL suppression inhibits a signaling pathway important to skeletal development and protein synthesis in osteoblasts, though raise that further investigations are essential to elucidate the exact mechanistic action of these proteins. The authors of this study suggest that NUMB constitutes a potential target for therapies targeting bone loss and reduced bone strength in patients with osteoporosis.